Harmonisasi Hukum Adat dan Hukum Positif dalam Pembagian Harta Perkawinan Antarsuku: Studi Kasus Sistem Patrilineal Batak dan Matrilineal Minangkabau - Al Khalifi, Annisa Bunga; Putra, Bryan Joseph; Zulfikar, Luthfi Naufan; Kelmanutu, Mervly Rumfiarsa; Ningthias, Nadya Ayu; Marsya, Revalina Zhalika; Cahayo, Raul Gindo (Media Hukum Indonesia (MHI), 2025)
In the context of Indonesia’s legal system, positive law, customary law, and religious law interact and often overlap in various aspects of social life. Customary law, including the patrilineal system of the Batak community and the matrilineal system of the Minangkabau community, dynamically interacts with positive law. This article employs a normative juridical approach to examine the differences in the principles governing marital property distribution under Batak (patrilineal) and Minangkabau (matrilineal) customary systems, as well as efforts to harmonize them with Law Number 1 of 1974 on Marriage. The findings indicate that, in Batak customary law, marital property generally belongs to the husband or the husband’s family based on patrilineal inheritance traditions. Meanwhile, Minangkabau customary law distinguishes between jointly acquired property (gono-gini) and individual inherited property, where the former is managed jointly and the latter remains the right of each spouse. Marriage Law 35-37 provide a framework for classifying assets (joint, separate, and acquired property), and Marriage Law 37 affirms that the division of joint property shall follow “the respective laws” of the parties, whether religious or customary. However, the absence of an implementing government regulation (as mandated by Marriage Law 67 No. 1/1974) and cultural diversity often lead to inconsistencies between customary and positive law. This article recommends a harmonization approach based on legal pluralism, recognizing and respecting customary rights insofar as they do not conflict with constitutional and human rights principles.